#### Answer

$g'(x)=2x-6x^2$

#### Work Step by Step

$g(x) = x^2(1-2x)$
Simplify
$g(x) = x^2-2x^3$
Power Rule
$g'(x) = 2x^{2-1}-2(3)x^{3-1}$
Simplify
$g'(x)=2x-6x^2$

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

$g'(x)=2x-6x^2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.